Multi‐Scale Imaging of Polymer Electrolyte Fuel Cells using X‐ray Micro‐ and Nano‐Computed Tomography, Transmission Electron Microscopy and Helium‐Ion Microscopy. Issue 1 (16th January 2019) - Meyer, Q.; Hack, J.; Mansor, N.; Iacoviello, F.; Bailey, J. J.; Shearing, P. R.; Brett, D. J. L.
Abstract: Multi‐length scale imaging of polymer electrolyte fuel cell (PEFC) membrane electrode assembly (MEA) materials is a powerful tool for studying, understanding and furthering improvements in materials engineering, performance and durability. A hot pressed MEA has been imaged using X‐ray micro‐ and nano‐computed tomography (CT), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and recently developed helium‐ion microscopy (HeIM). X‐ray nano‐CT captures a volume containing all of the relevant fuel cell interfaces, from the carbon fiber of the gas diffusion layer (GDL) to the Nafion membrane with a field‐of‐view of 5 µm and a pixel size of 64 nm. Features identified include linear marks on the carbon fiber surface, agglomerates of carbon nanoparticles in the microporous layer (MPL), and intrusion of the catalyst layer material into the Nafion membrane during the hot‐pressing process. HeIM has enabled imaging of a large area of MEA from tens of micrometers to sub‐nanometers pixel resolution without any sample preparation, and has captured similar features to X‐ray micro‐CT and nano‐CT. Furthermore, at its highest resolution, the platinum and carbon catalyst nanoparticles can be distinguished at the surface of the catalyst layer, overcoming the limitations of SEM and TEM.